Brain Atrophy in Iraqi Children Associated with Chromosome 6 Abnormality - Ahmed, Asma A; Barakat, Nadia T; Ali, Amal M; Ismail, Noor H; Yaseen, Nahi Y; Thaer, Noor; Muttlak, Fatimah A (Al-Nahrain Journal of Science, 2018)
Brain atrophy is one of the congenital malformations that increased recently among neonatal children in Iraq. Brain atrophy (BA) which means a decrease in size of brain or cells number caused by different factors one of them genetic factors. Since we lack the genetic bases on such cases, the objective of the study was to shed light on the impact of genetic factors causing brain atrophy. Chromosomal analysis was used to determine the genetic affecting alterations that may involve in brain atrophy. G-banding technique was used to diagnose chromosomal abnormalities in the thirty cases and their families. The results revealed different chromosomal abnormalities such as break, translocation and inversion (rearrangements) caused BA in children while their parents seemed with normal phenotype. In addition of deletion in the short arm of chromosome 6 which did not exceed globally 30 cases until 2005 was recorded. This deletion had a lethal effect on the new born baby with BA. Interestingly, this study showed a relationship between chromosome 6 and its effect on the safety of the brain.